Facilitators and barriers of children's participation in nutrition, physical activity, and obesity interventions: A systematic review. (1st September 2021) - Clayton, Priscilla; Connelly, Jeneene; Ellington, Malik; Rojas, Vicky; Lorenzo, Yaisli; Trak‐Fellermeier, María Angélica; Palacios, Cristina
Summary: Recruitment of children into clinical trials is challenging. Most systematic reviews exploring facilitators and barriers of child recruitment in clinical trials are related to drugs or experimental treatments for various health conditions. This may differ in nutrition, physical activity, and obesity interventions. The objective was to conduct a systematic review of facilitators and barriers for children's participation in nutrition, physical activity, and obesity interventions from the perspective of parents, children, and researchers. Studies were identified from five databases and restricted to children 2–18 years and the English language. Studies without results on facilitators and barriers of recruitment were excluded. Four hundred twenty‐three records were identified; 94 duplicates and 269 unrelated records were initially excluded; 60 records were reviewed for full‐text, and subsequently 34 were excluded, for a total of 26 included studies. The top barriers for recruiting children into clinical trials were time constraints, understanding of clinical trial information or complexity of consent/trial info, and transportation/lack of childcare. The most common facilitators were benefits to others and self, compensation/incentives, physician recommendations/referrals, and support. These barriers and facilitators should be addressed in future studies to assist in the successful recruitment of children into nutrition, physical activity, and obesity interventions.